Wounds and words: A lexical and syntactic analysis of Casocotâ€™s â€œThere are other things beside brightness and lightâ€ - Tarrayo, Veronico N. (Universitas Pendidikan Indonesia, 2020)
While there has been a sustained interest in conducting stylistic studies on fiction, specifically novels and short stories, the literature about stylistic analysis of flash fiction as a literary genre remains scant. Thus, the present study attempts to conduct a lexical and syntactic analysis of Ian Rosales Casocotâ€™s â€œThere Are Other Things Beside Brightness And Light.â€ The analysis was anchored in two of the four linguistic and stylistic categories proposed by Leech and Short (2007), namely lexical and grammatical. To communicate the narratorâ€™s traumatic experience, the following lexical categories were found: words that evoke the main characterâ€™s recollected sensations, particularly visual; a Latin expression, and slang words; concrete nouns providing access to the feelings of the main character; abstract nouns connoting psychological or emotional processes; and adjectives depicting sensory imageries and representing, along with some verbs, psychological states that carry negative connotations. Stative verbs vis-Ã -vis dynamic ones echo the impressions of attachment and detachment, and memory in the story, which link to the adverbs of manner in the text. On the other hand, these grammatical features contributed to text interpretation: cumulative or loose sentences depicting a series of rapid thoughts of the narrator who recalls a traumatic experience; mini-paragraphs, i.e., text fragmentation, foregrounding the theme of the narrative; a verb-tense shift from past to future, and the demonstrative pronouns that and this representing the struggle of the narrator to escape from the vexatious memory of pain and trauma; and the em dash paving the way for the narratorâ€™s emotional rumination. The stylistic analysis, particularly lexical and syntactic, provides a more objective and profound understanding of the underlying meanings of the FF under study.